Adhesive systems: a literature review (Research, Society and Development, 2021)
The adhesive systems are responsible for promoting the union between the dental substrate and the restoration itself. Since Buonocore, these materials have undergone important transformations. Therefore, the present study aims to review the literature on the classifications, main characteristics and action of current adhesive systems. It is a qualitative descriptive study, carried out through a bibliographic survey of scientific articles published in the last 11 years. Conventional adhesive systems are considered complex in clinical practice. The self-etchers, on the other hand, are easier to apply than the previous one and have good adhesion when selective enamel etching is performed. Meanwhile, universal adhesives have a more complex composition with a mixture of hydrophilic and hydrophobic monomers that promote chemical adhesion to the tooth. As for single-stage self-etching adhesives, the double application of the adhesive layer can improve the strength and quality of the adhesion. The universal adhesive has chemical bonding potential as an additional benefit, which depends on some functional monomers. Among them, the most notable is 10-methacryloyloxidecyl-dihydrogen (10-MDP or MDP), a phosphate monomer that binds ionically to dentin. Universal adhesives demonstrate good bond strength results in dentine that is already conditioned or not. Without selective acid attack, self-etching adhesives are inferior to conventional ones, already in prepared enamel, both are equivalent. Currently, it is possible to select the best adhesive system for each clinical reality, achieving good results even when you have time or resource limitations in your workplace.